Light harvesting and photoconversion efficiency enhancement in dye-sensitized solar cells via molecular and photonic advancements - Brown, M; Michael Brown (2012)
The main goal of this thesis is to investigate and develop the physics of dye-based photovoltaic physics through molecular and photonic routes. Numerous photovoltaics devices have been fabricated through the course of this work to study their characteristics, performance, physical composition and action. The relative youth of the field of dye-based optoelectronics provides extensive scope for new research which provides fascinating opportunities in terms of physical processes.This thesis is divided into two main projects; exploring the adaption of conventional dye-sensitized solar cells via starkly different routes which serendipitously culminated in striking similarities at their conclusion. The first route is through incorporating spectrally complementary dye molecules with the intention of extending the range of light absorption of the final devices. This initial aim was achieved and was then furthered by the realisation of an unexpected and unprecedented energy transfer process occurring, imparting enhanced photocurrent generation in both the near-IR and visibile region. The second route involves investigating the effect on dye-sensitized solar cell physics and performance of the inclusion of metallic nanoparticles with the expectation of inducing plasmonic interactions. Novel systems were designed and implemented, devices were made which display significant performance enhancement, attributed to plasmonic coupling into the dyes and thereby increasing photocapture. A number of other investigations are documented whose current completion does not sufficiently warrant independent chapters but whose scientific interest is evident.